(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
One could argue that the hardest part about science is reading the material. The vocabulary within the text is difficult, there are many graphs, pictures, equations, diagrams, and tables of information all added to enhance the text, but can be overwhelming (Mason & Hedin, 2011). With all of these various factors contributing to the complexity of science texts, how can students ever read a science text successfully? Through the utilization of literacy accommodations provided by the teacher, students in the regular education science classroom are capable of improving their academic achievement, especially in reading science texts. In this article, accommodations for science texts will be examined, and how these accommodations can fit into various types of instruction within a classroom.